The dynamic control ratio and its equilibrium point: A preliminary study of isokinetic fatiguing internal-external rotational effort of the shoulder joint in healthy subjects - Suzuki, Kodai; Okada, Takashi; Takayoshi, Hakkaku; Katz-Leurer, Michal; Dvir, Zeevi (Journal of Electromyography and Kinesiology, 2023)
The shoulder joint-related dynamic control ratio (DCR) is derived by dividing the peak eccentric moment of the external rotators (ER) by the peak concentric moment of the internal rotators (IR). However, given the inherent limitation associated with a single value DCR, an alternative approach is to calculate it at fixed angular intervals. This preliminary study aimed at exploring the variation in the DCR at a resolution of 1° and under fatiguing external and internal rotation exertions. Eighteen young men, 10 experienced and 8 without experience in overhead sporting activities completed two separate series of 45 ER eccentric and 45 IR concentric isokinetic repetitions at 120°/s. The analysis focused on repetitions 1–3 (TR1), 21–23 (TR2) and 41–43 (TR3). The relative fatigue values for both muscle groups and for both E and NE participants were 25–40% with significantly higher fatigue resistance in eccentric compared with concentric exertions. The DCR traces varied substantially linearly for most of the internal rotation range of motion while significant differences (p < 0.001) were found in their values within group between TR1, TR2 and TR3 and between experienced and non-experienced participants. An antagonistic moment equilibrium (DCR = 1) was reached in all instances and for both groups only during TR3 with a significant progressive reduction in this moment as fatigue increased. Thus, considering the DCR as an angle-based variable rather than a single value isokinetic parameter, may add new insight regarding the interplay between the rotatory muscles of the shoulder joint.